Preclinical Safety Assessment of a Highly Selective and Potent Dual Small-Molecule Inhibitor of CBP/P300 in Rats and Dogs. (April 2020) - Katavolos, Paula; Cain, Gary; Farman, Cindy; Romero, F. Anthony; Magnuson, Steven; Ly, Justin Q.; Choo, Edna F.; Katakam, Anand Kumar; Andaya, Roxanne; Maher, Jonathan
Cyclic adenosine monophosphate-response element (CREB)-binding protein (CBP) and EP300E1A-binding protein (p300) are members of the bromodomain and extraterminal motif (BET) family. These highly homologous proteins have a key role in modulating transcription, including altering the status of chromatin or through interactions with or posttranslational modifications of transcription factors. As CBP and p300 have known roles for stimulating c-Myc oncogenic activity, a small-molecule inhibitor, GNE-781, was developed to selectively and potently inhibit the CBP/p300 bromodomains (BRDs). Genetic models have been challenging to develop due to embryonic lethality arising from germline homozygous mutations in either CBP or P300. Hence, the purpose of this study was to characterize the role of dual inhibition of these proteins in adult rats and dogs. Repeat dose toxicity studies were conducted, and toxicologic and pathologic end points were assessed. GNE-781 was generally tolerated; however, marked effects on thrombopoiesis occurred in both species. Evidence of inhibition of erythroid, granulocytic, and lymphoid cell differentiation was also present, as well as deleterious changes in gastrointestinal and reproductive tissues. These findings are consistent with many preclinical (and clinical) effects reported with BET inhibitors targeting BRD proteins; thus, the current study findings indicate a likely important role for CBP/p300 in stem cell differentiation.